2013
DOI: 10.1016/j.smim.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of the complement system in metabolic organs and metabolic diseases

Abstract: Emerging evidence points to a close crosstalk between metabolic organs and innate immunity in the course of metabolic disorders. In particular, cellular and humoral factors of innate immunity are thought to contribute to metabolic dysregulation of the adipose tissue or the liver, as well as to dysfunction of the pancreas; all these conditions are linked to the development of insulin resistance and diabetes mellitus. A central component of innate immunity is the complement system. Interestingly, the classical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 122 publications
6
112
0
Order By: Relevance
“…Indeed, complement activation in a colitis-associated cancer model induced by combined administration of azoxymethane and dextran sulfate sodium has been shown to result in the induction of the pro-inflammatory cytokine IL-1β, mainly by infiltrating neutrophils and consequent production of IL-17, a major inducer of intestinal disease 79 . Supporting the correlation between imbalanced complement activation, inflammation and intestinal tumorigenesis, an elegant study using a model of diet-induced intestinal tumorigenesis in genetically susceptible Apc Min /+ mice has demonstrated that the source of dietary fat, and not obesity itself, triggers complement activation, inflammation, expression of oncogenes and intestinal polyposis; obesity and its associated metabolic changes had previously been associated with imbalanced complement activation, inflammation and cancer 80,81 . However, the Apc Min /+ study dissociated the direct link between obesity and cancer by showing that whereas obese mice showed increased tumorigenesis when fed a high-fat diet containing fat derived from corn and coconut oil, intestinal polyposis was not observed in obese mice who were fed a high-fat diet consisting of fat from olive oil 82 .…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 99%
“…Indeed, complement activation in a colitis-associated cancer model induced by combined administration of azoxymethane and dextran sulfate sodium has been shown to result in the induction of the pro-inflammatory cytokine IL-1β, mainly by infiltrating neutrophils and consequent production of IL-17, a major inducer of intestinal disease 79 . Supporting the correlation between imbalanced complement activation, inflammation and intestinal tumorigenesis, an elegant study using a model of diet-induced intestinal tumorigenesis in genetically susceptible Apc Min /+ mice has demonstrated that the source of dietary fat, and not obesity itself, triggers complement activation, inflammation, expression of oncogenes and intestinal polyposis; obesity and its associated metabolic changes had previously been associated with imbalanced complement activation, inflammation and cancer 80,81 . However, the Apc Min /+ study dissociated the direct link between obesity and cancer by showing that whereas obese mice showed increased tumorigenesis when fed a high-fat diet containing fat derived from corn and coconut oil, intestinal polyposis was not observed in obese mice who were fed a high-fat diet consisting of fat from olive oil 82 .…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 99%
“…As many studies have demonstrated, increased C3 levels, such as those found in obese persons, automatically give rise to higher levels of C3a-desArg, which can affect adipocytes and macrophages in the adipose tissue (Mamane et al, 2009). It is conceivable that the turnover of C3 also results in an activation of C5 and that the anaphylatoxins C3a and C5a, acting via the C3aR, C5aR1, and C5aR2 receptors, cause low-grade inflammation (Phieler et al, 2013a(Phieler et al, , 2013b. This possibility is corroborated by the fact that in lean individuals, adipose tissue preferentially releases anti-inflammatory adipokines such as transforming growth factor beta (TGF-beta) (Ailhaud et al, 1992), interleukin (IL)-10, IL-4, IL-13, IL-1 receptor antagonist (IL-1Ra), and adiponectin (Maeda et al, 1996), whereas in obesity, adipose tissue secretes proinflammatory cytokines, among which are IL-6 (Mohamed-Ali et al, 1997), INF-␥, TNF, IL-␤, (Hotamisligil et al, 1993), angiotensin II, leptin (Caro et al, 1996), resistin, vistafin, and plasminogen activator inhibitor 1 (Ouchi et al, 2011).…”
Section: Macrophages and Inflammation In Adipose Tissuementioning
confidence: 99%
“…This response can be driven, or at least supported, by C5a generation (Samad and Ruf, 2013). This inflammation and the insulin resistance are partially induced by the C5aR1 (Phieler et al, 2013a(Phieler et al, , 2013b. The increased levels of C3a-desArg also affect the adipocytes, accelerating triglyceride metabolism and increasing triglyceride levels in the plasma, and thereby explaining the elevated triglyceride levels and insulin resistance seen in individuals with obesity and the MetS.…”
Section: Macrophages and Inflammation In Adipose Tissuementioning
confidence: 99%
“…This occurs via the effect of C3a/5a receptor signaling on cytokine and transcription factor expression 74,75 . Complement, (principally C3a and C5a) has also been implicated in the regeneration of bone, cardiac muscle and skeletal muscle, as well as stem cell engraftment (reviewed in 76-78 ). Additionally, several groups have reported that complement also plays an important role in several key processes in the central nervous system (CNS) 77-79 .…”
Section: Functions Of the Complement Systemmentioning
confidence: 99%